Human capital, social capital, participation and cooperative performance among cooperative board members in Program Desa Lestari, Malaysia - Buang, Mokhtaruddin (2021)
In Malaysia, co-operatives have played a significant role in the government's rural community development agenda. With the introduction of Program Desa Lestari in 2013, the government has strengthened the use of the co-operative platform to improve the rural community's well-being. Nonetheless, the platform's viability as a strategy for this programme is contingent on the effectiveness of the co-operative board members' roles. Hence, the effectiveness of co-operative board members is examined in this thesis via the lens of the resource provision role of the board members' human capital and social capital, which would influence on the co-operative's performance in Program Desa Lestari. Besides, board participation was proposed as a mediating factor of the relationship between human capital and social capital on co-operative performance. Subsequently, the Resource Dependence Theory and Participation Theory were integrated in order to better understand the impact of these factors on the performance of the co-operatives in Program Desa Lestari. A proportionate stratified sampling procedure was used, and data was obtained from questionnaires sent online and via mail. After the data screening process, 226 responses were received involving 38 co-operatives for analysis. Statistical Package for Social Science (SPSS) and the Partial Least Square Structural Equation Modeling (PLS-SEM) data analysis technique was used to analyse the data. Two types of data analysis were conducted; first, the descriptive analysis to determine the level of all related variables; and second, the inferential analysis using PLS-SEM to examine four hypotheses drawn from the research model. This research revealed several noteworthy findings; first, it was discovered that the majority of the co-operatives (ƒ =21) performed at an average to very satisfactory level (51% and above), with 9 co-operatives operating under the functions of service. Meanwhile, 17 co-operatives were classified as having unsatisfactory to very unsatisfactory performance, with a score of 50% and below. Overall, the finding showed that co-operative performance in Program Desa Lestari is moderate. Second, this study found that the respondents of this study claimed to have a high level of human capital, social capital, and participation. Third, the PLS-SEM analysis showed that despite the level of human capital and social capital of the respondents were high in this study, these constructs had no relationship on co-operative performance, as evidenced by the effect size (q2) analysis (human capital = 0.016; social capital = 0.007). Fourth, the bootstrapping analysis indicated that board participation had no effect on the relationship between human and social capital and cooperative performance. Finally, the finding reported that all the variables explained 12.4% of the variance in co-operative performance in the current study. Although the findings were found not statistically insignificant, the present study's model was predictively accurate, as evidenced by Q2 values greater than 0. Based on these findings, the proposed theoretical framework serves as a prospective research since it is the first to integrate the Resource Dependence Theory and the Participation Theory in investigating the effectiveness of board members on co-operative performance. Hence, this framework offers empirical and theoretical ground for future research, especially in the context of co-operatives, in order to highlight the viability of this platform as a community development strategy.